تقييم جودة الخدمة لشبكات MPLS-DiffServ - أحمد أحمد; طلال العاتكي; منهل جعفر (Tishreen University, 2016)
The desire to improve the overall performance of IP network leads to designing new QoS achitectures. The new Enhancement in providing quality of service (QoS) on the Internet is based on the Different Services (DiffServ). DiffServ divides traffic into small classes and allocates network resources on a per-class basis. In this architecture, packets are marked with different DiffServ code points (DSCP) at edge routers, and the priority for packets is given via the value of this field. On the other hand, MPLS is a fast forwarding mechanism that depends on Label's. The main advantage of MPLS is its support for traffic engineering which results in best utilization of network's resources like link capacity. The integration of using MPLS (as a forwarding mechanism) with DiffServ (as a QoS mechanism) offer high Quality of service especially for real time applications (such as VoIP, Video Conference). We evaluate the performance of MPLS-DiffServ networks in our research. We study QoS metrics as delay, variation of delay, upload response time, link utilization, packet loss for several kinds of traffic (Voice, Video, FTP) by using OPNET Simulator and we showed its superiority over MPLS network and pure IP ones. We compare our results with MPLS networks and pure IP ones. Our results showed superiority of MPLS-DiffServ over other kinds of networks. This is clear in decreasing delay ,delay variation, upload response time, queuing delay, reduction of lost packets and best utilization of link capacity دفعت الرغبة لتحسين الأداء الكُلّي لشبكات IP إلى إنشاء بنى QoS جديدة. التطور الحاصل حاليا في تأمين جودة الخدمة مبني على DiffServ . تقسّم DiffServ الحركة إلى عدد صغير من الأصناف وتقوم بحجز المصادر على أساس كل صنف. في هذه البنية تُعلّم الرزم بناءً على حقل DSCP في الموجهات الطرفية ويتم كذلك إعطاء الأولوية للرزم بناء على قيمة هذا الحقل. بالمقابل, فإن MPLS هي آلية توجيه سريعة تعتمد على الوسوم. من مزايا MPLS الرئيسية دعمها لهندسة الحركة والذي يؤدي إلى استخدام أفضل لمصادر الشبكة مثل سعة الوصلة. يؤمن الاستخدام المتكامل لـ MPLS (كآلية إرسال) مع DiffServ (كآلية QoS) ضماناً لتقديم جودة خدمة عالية وخاصة بالنسبة لتطبيقات الزمن الحقيقي (مثل خدمة الصوت عبرIP ومؤتمرات الفيديو). تم في بحثنا هذا تقييم أداء شبكات MPLS-DiffServ, قمنا بدراسة بارامترات جودة الخدمة مثل التأخير وتغير التأخير وزمن تحميل الملفات وزمن الترتيل واستخدام الوصلة والإنتاجية وفقدان الرزم لأنماط متعددة من الحركة (Voice,Video,FTP) وذلك باستخدام محاكي OPNET. تمت مقارنة النتائج مع شبكات MPLS وشبكات IP الصافية. أظهرت النتائج تفوق شبكات MPLS-DiffServ على الشبكات الأخرى ويبدو ذلك واضحا من ناحية تخفيض التأخير وتغير التأخير وزمن الاستجابة لتحميل الملفات وزمن الترتيل بالإضافة إلى انخفاض ضياع الرزم والاستخدام الأمثل لسعة الوصلة.